2022
DOI: 10.3390/rs14122926
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Based Unconstrained Step Detection Fusing a Variable Sliding Window and an Adaptive Threshold

Abstract: Step detection for smartphones plays an important role in the pedestrian dead reckoning (PDR) for indoor positioning. Aiming at the problem of low step detection accuracy of smartphones in complex unconstrained states in PDR, smartphone-based unconstrained step detection method fusing a variable sliding window and an adaptive threshold is proposed. In this method, the dynamic updating algorithm of a peak threshold is developed, and the minimum peak value filtered after a sliding window filter is used as the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Using fixed peak value and time threshold constraint will not satisfy the step counting accuracy under various motion states. Fast Fourier transform (FFT) can convert time domain signals into frequency domain signals 15 , so this paper gathered 5 volunteers to test and analyze step frequency under different motion states based on FFT algorithm. After the test of 5 volunteers, we found that the step frequency of walking at normal walking was 1.4-1.8Hz, corresponding to about 0.55-0.71s.…”
Section: Step Frequency Detectionmentioning
confidence: 99%
“…Using fixed peak value and time threshold constraint will not satisfy the step counting accuracy under various motion states. Fast Fourier transform (FFT) can convert time domain signals into frequency domain signals 15 , so this paper gathered 5 volunteers to test and analyze step frequency under different motion states based on FFT algorithm. After the test of 5 volunteers, we found that the step frequency of walking at normal walking was 1.4-1.8Hz, corresponding to about 0.55-0.71s.…”
Section: Step Frequency Detectionmentioning
confidence: 99%
“…Integration of part into T_set tuple (19) else if (20) Integration of intersect (part, IP) into I_set tuple (21) end if (22) end for (23) are mainly used in the study as the main factors to measure the temporal characteristics. However, the window size and input threshold set in the sliding window algorithm also have an impact on the fnal compression efect [36,37].…”
Section: Trajectory Compression Of Critical Regions Considering Spati...mentioning
confidence: 99%
“…Therefore, some scholars combine wireless indoor positioning algorithms with pedestrian dead reckoning (PDR) algorithms to achieve continuous and accurate indoor positioning [7][8]10,21]. The PDR algorithm can only rely on the IMU sensor embedded in the smartphone to estimate the direction and distance of the movement of the moving target and calculate the location of the moving target [7,22]. Accordingly, PDR cannot be affected by NLOS.…”
Section: Introductionmentioning
confidence: 99%